2020
DOI: 10.1186/s12890-020-1062-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomarker genes which distinguish between smokers and chronic obstructive pulmonary disease patients with machine learning approach

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is combination of progressive lung diseases. The diagnosis of COPD is generally based on the pulmonary function testing, however, difficulties underlie in prognosis of smokers or early stage of COPD patients due to the complexity and heterogeneity of the pathogenesis. Computational analyses of omics technologies are expected as one of the solutions to resolve such complexities. Methods: We obtained transcriptomic data by in vitro testing with exposures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…To reduce the dependence on lung function tests for early diagnosis of COPD, ML has also been used to mine and analyze transcriptomic data extracted from human bronchial epithelial cells, leading to the identification of abnormal expression of 15 genes in the disease, 10 of which had not previously been reported as COPD biomarkers. The different gene combinations were then analyzed by the random forest algorithm to distinguish non-smokers from smokers and COPD patients 74 ( Table 3 ). Despite the remarkable diagnostic accuracy of each subgroup (65%), further studies are required to improve the model performance in distinguishing COPD patients from smokers without COPD.…”
Section: Ai/ml and Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the dependence on lung function tests for early diagnosis of COPD, ML has also been used to mine and analyze transcriptomic data extracted from human bronchial epithelial cells, leading to the identification of abnormal expression of 15 genes in the disease, 10 of which had not previously been reported as COPD biomarkers. The different gene combinations were then analyzed by the random forest algorithm to distinguish non-smokers from smokers and COPD patients 74 ( Table 3 ). Despite the remarkable diagnostic accuracy of each subgroup (65%), further studies are required to improve the model performance in distinguishing COPD patients from smokers without COPD.…”
Section: Ai/ml and Copdmentioning
confidence: 99%
“…The size of trees and the number of variables usually determine the performance of model. [27,28,30], [47,48,59], [65][66][67]74,79], [90,99,101], [104,107,109] Support vector machine Support vector machine is usually used for classification and regression. It learns the optimal hyperplane to classify data.…”
Section: General Concepts Terminologies and Limitations Of Ai/mlmentioning
confidence: 99%
“…Paradoxically, in terms of current medications for asthma/COPD, a risk factor for both COPD and lung cancer is upregulation of the ADRB2 gene for sympathetic ÎČ2 receptors, with downregulation of this gene activity associated with better squamous-cell cancer survival [76]. Using 3D epithelial cell culture, MATSUMURA et al [77] exposed cells to oxidant stress and found 15 genes were perturbed, with those for cell proliferation and redox homeostasis being downregulated; however, EMT-related genes (including for epidermal growth factor receptor (EGFR)) were upregulated and this was especially marked in cells from smokers and COPD patients.…”
Section: Epithelial-mesenchymal Transition and Insights Into Its Role In Driving Airflow Obstructionmentioning
confidence: 99%
“…Machine learning approaches can also exploit the richness of gene expression data to assist in COPD diagnostic and prognostic tasks. In recent work, a random forest was used to classify airway transcriptomic data from 15 pre-selected candidate genes to define a COPD risk score 65 . Although the ability to discriminate COPD subjects was very limited, active research in exploiting omics data with machine learning may offer new insights about disease pathogenesis.…”
Section: Diagnosis and Outcome Predictionmentioning
confidence: 99%